Multicultural Character Education in the 21st Century: Lessons from Indonesian Pesantren for Global Educational Development - Yassir Hafidh Fitriyan; Triono Ali Mustofa; W Waston; Ahmad Akbar Fauzi; Nurul Asma Khoiriyah (Universitas Muhammadiyah Surakarta, 2025)
The 21st century's digital disruption, intensified mobility, and the resurgence of identity-based polarization have reconfigured the aims of education beyond cognitive achievement toward ethical agency, intercultural competence, and socially responsible citizenship. This article examines how Indonesian pesantren-Islamic boarding schools with a long tradition of moral formation-cultivate multicultural character and what lessons their value-based ecology offers for global educational development. Using library research, the study conducts a philosophical and conceptual content analysis of peer-reviewed scholarship, pesantren-related policy and curricular documents, and global education frameworks, especially Global Citizenship Education and Education for Sustainable Development. The synthesis indicates that pesantren operationalize multicultural character through (1) ethical-theological foundations such as rahmatan lil 'alamin and ukhuwah insaniyah, (2) communal pedagogies emphasizing exemplary leadership (uswah), habituation, and community learning, and (3) adaptive innovations that integrate digital literacy with moral restraint. These practices foster moderation, empathy, inclusivity, and civic responsibility-capabilities aligned with 21st-century learning agendas. The article proposes a Pesantren-Based Multicultural Character Education Model (PBMCEM) as a transferable conceptual framework. Implications are discussed for curriculum design, teacher formation, and policy, highlighting how localized religious-moral traditions can inform internationally relevant strategies for multicultural character education.